Survey of several key technologies for 5G - Ping ZHANG; Yun-zheng TAO; Zhi ZHANG (Tongxin xuebao)
The fifth-generation (5G) mobile communications system has got extensive attention and research by enter-prises, research institutes and universities of the world at present. The development history and domestic and abroad re-search progresses of 5G were described and summarized in detail. 5G network architecture based on virtualization were analyzed. From wireless transmission, wireless access and network perspectives, the potential key technologies of 5G, in-cluding massive MIMO, full-duplex, channel modeling, channel coding, etc. and their latest progress are introduced comprehensively and thoroughly. Some advantages, disadvantages and future research directions of some key technolo-gies are analyzed. At last, key tasks and main directions of the future development of 5G are prospected.